Extended Adjuvant Endocrine Therapy After Breast Cancer: “Longer Is Better” - de la Noval, Begoña Díaz (International Journal of Innovative Research in Medical Science, 2016)
Recent evidence supports the use of extended adjuvant endocrine therapy (EAET) with either Tamoxifen (TMX) or an Aromatase Inhibitor (AI) after five years of initial adjuvant TMX to reduce BC recurrence and mortality in women with hormone-receptor positive early-stage breast cancer. This manuscript wants to give a brief overview of published data and ongoing studies concerning extended adjuvant endocrine therapy. Premenopausal women should be treated with 10 years of Tamoxifen. Current strategies for postmenopausal women include initial adjuvant AI therapy, sequential AI therapy after 2 to 3 years of tamoxifen, or extended AI use after 5 years of TMX. However, data from trials looking at prolonged AI therapy beyond 5 years are required to determine the optimal total duration of AI therapy. In cases of recommending extended endocrine therapy with AI, Letrozole is first line treatment; Exemestane and Anastrozole still require research. Future studies are required; emphasis should be laid on who should use which drug, and for how long.